Peningkatan Kapasitas Bisnis Berbasis Komunitas dan Mitigasi Sampah melalui Produk Konversi pada Bank Sampah Sinar Berlian - Budiman, Eko Wahyu; Pitaloka, Dyah; Masrunik, Endah; Puspitorini, Palupi; Sunandes, Aris; Endrawati, Tri (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service was carried out in Gedog Village, Blitar City. The purpose of the service was to increase the capacity of household waste management and waste mitigation through conversion products and community-based business management at the "Sinar Berlian" Waste Bank in Blitar City. This activity was motivated by the high volume of inorganic waste at the Sinar Berlian Waste Bank and its surroundings and the low participation of residents in waste management. Therefore, through this service, the PKM program was provided to provide solutions to existing problems. The methods used included program socialization, community-based production and management training, technical assistance, and marketing digitalization. The main activities included training in making pressed plastic, sorting plastic waste, community-based management, and digital-based marketing. The final results of this service activity showed that this activity successfully reached a total of 72 active participants, with a predominance of women (68%). The attendance rate reached 85%, indicating the enthusiasm and commitment of participants in absorbing the training materials. In the production sector, the production volume of pressed plastic increased 300%, 1000kg per month up to 3000 kg per month. Income increased by 84.37% compared to before the intervention. Community-based management has succeeded in coordinating 6 other Waste Banks in increasing their production capacity and income. Collaboration was implemented in the form of logistics sharing, namely the acquisition of used plastic bottles and the aggregation of press plastic sales. Participants' understanding was evaluated through pre- and post-tests, which showed an increase in scores from 46% to 82%. This demonstrates the effectiveness of the PRA training method and approach in delivering material in a practical and applicable manner. This program contributes to community-based sustainable environmental management practices and can be replicated in other areas with similar issues.